2013
DOI: 10.1002/jcp.24471
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Isolation, and Culture of Mouse and Human Spermatogonial Stem Cells

Abstract: Spermatogenesis is a special process by which spermatogonial stem cells (SSCs) divide and differentiate to male gametes called mature spermatozoa. SSCs are the unique cells because they are adult stem cells that transmit genetic information to subsequent generations. Accumulating evidence has demonstrated that SSCs can be reprogrammed to acquire pluripotency to become embryonic stem-like cells that differentiate into all cell lineages of the three germ layers, highlighting potential important applications of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 98 publications
0
40
0
2
Order By: Relevance
“…2 Lin28 was used as a SSCs marker in the previous studies and has been shown to be associated with stemness of SSCs. 36, 37, 38, 39, 40 In our experiments, Lin28 was used to distinguish the undifferentiated spermatogonia from other types of cells(such as Sertoli cell and differentiated spermatogonia).The result showed that Lin28-positive cells in ESET-KD group were significantly reduced (Figure 2e), suggesting ESET deficiency led to decrease of the number of SSCs probably because of apoptosis or differentiation.…”
Section: Resultsmentioning
confidence: 78%
“…2 Lin28 was used as a SSCs marker in the previous studies and has been shown to be associated with stemness of SSCs. 36, 37, 38, 39, 40 In our experiments, Lin28 was used to distinguish the undifferentiated spermatogonia from other types of cells(such as Sertoli cell and differentiated spermatogonia).The result showed that Lin28-positive cells in ESET-KD group were significantly reduced (Figure 2e), suggesting ESET deficiency led to decrease of the number of SSCs probably because of apoptosis or differentiation.…”
Section: Resultsmentioning
confidence: 78%
“…The expression profile of miRNAs in testes is given in Table 1. miRNA and spermatogonial stem cell renewal Within the testis, the SSCs reside in a unique microenvironment, or 'niche', which includes the surrounding somatic cells. Spermatogenesis originates from SSCs, which have the dual property of continually renewing and undergoing differentiation into a spermatogonial progenitor that expands and further differentiates (Hess et al 2006, Ventela et al 2012, Dovere et al 2013, Silvan et al 2013, van den Driesche et al 2014, Guo et al 2014. In the rodent testis, SSCs are among undifferentiated spermatogonia that include Asingle (As), Apaired (Apr), and Aaligned (Aal) spermatogonia (Dym 1994).…”
Section: Expression Profile Of Mirna In the Testismentioning
confidence: 99%
“…Additionally, mGSCs were obtained from mouse testes, and they are morphologically similar to embryonic stem cells (ESCs) and contribute to embryonic development following microinjection into blastocysts (Oatley et al 2006;Dym et al 2009;He et al 2010). A long or short term culture system for mGSCs has been established for human, mouse, and other mammals (Akhondi et al 2013;Guo et al 2014). The cultured mGSCs also express the markers of SSCs, and differentiated into spermatozoa.…”
Section: Introductionmentioning
confidence: 99%